Maxillary and Mandibular Occlusal Photographs - Marcos A. Vargas, DDS, MS (Journal of Prosthodontics, 2003)
INTRAORAL OCCLUSAL photographs, both maxillary and mandibular, are frequently a necessary part of the standard patient record in clinical dental practice.